TRANSAKSI PINJAMAN PAY LATER PADA MARKETPLACE SHOPEE PADA PERSPEKTIF HUKUM EKONOMI ISLAM - Eka Junila Saragih (Fakultas Syariah (Syari'ah Faculty ), 2021)
This article aims to examine the loan on the pay later feature provided by the shopee marketplace. Shopeepaylater provides assistance in the form of instant loans for users who want to buy the desired item. Loans provided cannot be cashed and can only be used at the shopee marketplace. To get a shopeepaylater loan limit, the user must meet the requirements set by Shopee. The nominal loan limit given to each user is different. The terms of the loan service provided are in the form of 1x installment/Buy now, pay later and in installments of 2 months, 3 months, 6 months and 12 months. This research uses an empirical method that is descriptive with a qualitative approach. The primary data source in this study were shopeepaylater users. Meanwhile, secondary data were obtained from related books and documents. The loan between the borrower and the shopee have met the pillars and qardh requirements. However, in determining the handling fee, the shopee sets the fee as a percentage. Based on the Fatwa of the National Syari'ah Council NO.19/DSNMUI/IV /2001 concerning Al-Qardh, does not allow handling or administration fees based on calculating a percentage of the amount of qardh funds given. There are differences opinion of credit practice to conclude, credit practices are not allowed as there is an additional price is usury, while usury is prohibited in islam. Some opinion that allow the credit practice is clear on the grounds of the akad. Because they observe from the general proposition that allows. As long as the additional price on the postponement is a fair and reasonable price, and there is no coercion both sides.